2015
DOI: 10.1021/acs.analchem.5b02846
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Silane Molecules on Oxidized Silicon: Are there Options for a Traceable and Absolute Determination?

Abstract: Organosilanes are used routinely to functionalize various support materials for further modifications. Nevertheless, reliable quantitative information about surface functional group densities after layer formation is rarely available. Here, we present the analysis of thin organic nanolayers made from nitrogen containing silane molecules on naturally oxidized silicon wafers with reference-free total reflection X-ray fluorescence (TXRF) and X-ray photoelectron spectroscopy (XPS). An areic density of 2-4 silane m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 91 publications
4
34
0
Order By: Relevance
“…Studies of amine and carboxylic acid functionalized polymer and clay NPS have determined that anywhere from a few percent to approximately all of the functional groups can be covalently modied. 2,7,18,43,44 With the exception of an assay based on reaction of maleimide with cysteine, 45 most studies have reported covalent modication of low fractions of total amine with larger probes or reagents generally having lower coupling efficiency. The results in Table 1 demonstrate that a minimum of 50% of total amines react with the reagents used for the two colorimetric assays for silica NPs, with over 70% modication achieved for most samples.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of amine and carboxylic acid functionalized polymer and clay NPS have determined that anywhere from a few percent to approximately all of the functional groups can be covalently modied. 2,7,18,43,44 With the exception of an assay based on reaction of maleimide with cysteine, 45 most studies have reported covalent modication of low fractions of total amine with larger probes or reagents generally having lower coupling efficiency. The results in Table 1 demonstrate that a minimum of 50% of total amines react with the reagents used for the two colorimetric assays for silica NPs, with over 70% modication achieved for most samples.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Figures 5b and 5c show the XPS full spectrum and high-resolution spectrum of Si 2p core-level peak for the PBI-DIm-Si hybrid membrane. The Si 2p peak can be deconvoluted into two sub-peaks at 101.7 eV for silane and 103.3 eV for silica [51], revealing that the partial silicon element was converted from organic silane to inorganic silica. This result confirmed the formation of the silica-based component in the hybrid membrane.…”
Section: Membrane Morphologymentioning
confidence: 99%
“…was referenced to main O 1s peak component of molecular O 2 located at 539.3 eV[25,26] 2. A relative uncertainty of 20% has to be considered for the relative peak component areas[31,32] 3. B.E.…”
mentioning
confidence: 99%